Low-Cost Domestic Wastewater Pollution Monitoring System in Residential Areas using IoT: Case Studies in Bandung Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Monitoring and controlling river pollution from domestic waste is currently a crucial part of urban community development. Nowadays, it is difficult to determine the source of pollutants in the river because data on the number of domestics that dispose of wastewater into rivers is still very limited. Surface water samples are tested by environmental laboratories only twice a year, or based on requests from interested parties such as companies, factories, local government, and local police departement based on suspicion or reports of suspected waste disposal in specific areas. However, during our sampling, it often occurs that the river water to be tested has returned to normal because the wastewater discharged by the domestic waste has already flowed downstream, especially in the rainy season. Therefore it is necessary to monitor in a situation that can measure the quality of river water, estimate the source of pollutants, and monitor the time of taking river water properly so that monitoring and control of river pollution can be carried out. The Internet of Things technology enables local governments to record river or ditch water quality faster through sensors of water temperature, turbidity, total dissolved solids, pH, air temperature, water level, and rain. With the Decision Tree C4.5 algorithm, successful data recorded can be analyzed to present the highest contamination time. This time of highest contamination can be used as a recommendation for sampling time for laboratory test results. The combination of Internet of Things technology, Rest API, and Decision Tree C4.5 can produce a monitoring System for river and ditch water content used for monitoring and controlling water pollution